2018
DOI: 10.1007/s00348-018-2490-7
|View full text |Cite
|
Sign up to set email alerts
|

Oil/water displacement in microfluidic packed beds under weakly water-wetting conditions: competition between precursor film flow and piston-like displacement

Abstract: Optical microscopy was used to measure depth-averaged oil distribution in a quasi-monolayer of crushed marble packed in a microfluidic channel as it was displaced by water. By calibrating the transmitted light intensity to oil thickness, we account for depth variation in the fluid distribution. Experiments reveal that oil saturation at water breakthrough decreases with increasing Darcy velocity, U w , between capillary numbers Ca = w U w ∕ = 9 × 10 −7 and 9 × 10 −6 , where w is the dynamic viscosity of water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Previous studies also showed a weak dependence of ROS on Ca. Krummel et al (2013) found that ROS decreases significantly for Ca larger than 2 × 10 -4 but not for lower capillary numbers as used in our study (Krummel et al 2013;Tanino et al 2018). It is worth noting here that our findings were made at comparable capillary numbers but for smaller pore sizes and a higher (oil:water) viscosity ratio.…”
Section: Waterflooding Experimentsmentioning
confidence: 40%
See 1 more Smart Citation
“…Previous studies also showed a weak dependence of ROS on Ca. Krummel et al (2013) found that ROS decreases significantly for Ca larger than 2 × 10 -4 but not for lower capillary numbers as used in our study (Krummel et al 2013;Tanino et al 2018). It is worth noting here that our findings were made at comparable capillary numbers but for smaller pore sizes and a higher (oil:water) viscosity ratio.…”
Section: Waterflooding Experimentsmentioning
confidence: 40%
“…The effective pixel size was 0.135 × 0.135 µm. The middle regions of the packed beds were visualized, while the downstream regions (300-400 µm close to the pillars) were excluded to avoid end effects (Tanino et al 2018). At each (X, Y) ROI, a series of images along the Z-direction was recorded over a range of 25 µm (in steps of 330 nm), at an exposure time of 100 ms per image.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…They used soda line glass spheres to represent silica; however, for other minerals they crushed rock or crystals. Tanino et al [ 137 , 138 ] used a similar micromodel with quasi-monolayer of crushed marble packed inside a channel to study mixed-wet conditions on oil recovery and film flow and piston-like displacement in oil/water two-phase flow. They used a variable wavelength light source and a high-speed 24-bit colour camera coupled with an optical microscope to image the depth-integrated fluid distribution.…”
Section: Microfluidic Devices (Physical Micromodels Of Porous Geommentioning
confidence: 99%
“…Fabrication of geomaterial microfluidics has received attention in the fields of hydrology and petroleum engineering, in which pore-scale flow and/or transport is often dictated by surface chemistry (Bowden et al 2016;Gerami et al 2017;Mahoney et al 2015Mahoney et al , 2017Morais et al 2016;Oh et al 2017;Porter et al 2015b;Song et al 2014;Tanino et al 2018;Wang et al 2017;Zhang et al 2018). In Fig.…”
Section: Geomaterials Microfluidicsmentioning
confidence: 99%